Catalyst free synthesis of 2‐Aryl‐2H‐benzo[b][1, 4]oxazines and 3‐Aryl‐2H‐benzo[b][1, 4]thiazin‐2‐ones: An ultrasonication‐assisted strategy. (13th April 2021) - Teli, Bisma; Waseem, Malik Abdul; Rashid, Showkat; Ganaie, Bilal Ahmad; Bhat, Bilal A.
Abstract: An ultrasonication‐assisted synthesis of 2‐Aryl‐2 H ‐benzo[ b ][1, 4]oxazines and 3‐aryl‐2 H ‐benzo[ b ][1, 4]thiazin‐2‐ones has been established by reacting phenacyl bromides with 2‐aminophenol and 2‐aminothiophenol, respectively. This approach fosters flexibility in generating a diverse range of 1, 4‐benzoxazines and 1, 4‐benzothiazinones under catalyst‐free reaction conditions. Further scope toward the synthesis of rarely occurring bis ‐benzoxazine adduct has also been explored, which enabled us to propose the reaction mechanism. Abstract :